Legalizing speed Endurance Training According to Some Physiological Indicators for 800-Meter Runners for Youth (Indian Journal of Forensic Medicine & Toxicology, 2020)
The importance of research lies in the preparation and codification of speed endurance exercises accordingto some physiological indicators for 800-meter runners for youth and to identify the effect of codifying speedendurance training according to some physiological indicators of 800 meters for youth, as the researcheradopted the experimental approach in designing the two equivalent groups (control and experimental) to suitthe nature of the research, where the research sample was determined by deliberate selection of young runnersin athletics at the age of (18-19 years) according to the classification of the international athletics federation,as the research sample included (10) runners representing Baghdad clubs who were distributed randomly (bylot) into two groups control and experimental group each consisting of (5) runners, physiological tests wereperformed, including the maximum consumption of oxygen and lactic acid, and the physical tests included(1000) meter endurance test and (800) meter achievement test on the research sample, and the researchercame to the following conclusions that the speed endurance training gave progress in the level of the (800)meter running in this test, and they need to be stable and avoid fluctuation in the variation in the values of thistest, the results showed that the experimental group members outperformed the control in the physiologicalindicators (lactic acid concentration, the maximum oxygen consumption (VO2max) in the post-tests. Theresearcher recommended the necessity of conducting physiological tests to legalize training loads because oftheir effective role in the training process, focusing on developing and rationing the speed bearing capacitybecause of its direct impact on the development of achievement in the activities of middle-distance athletics.